2015
DOI: 10.1038/jid.2015.240
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Alopecia and Abnormal Epidermal Cornification in Zdhhc13 -Deficient Mice Reveal the Importance of Palmitoylation in Hair and Skin Differentiation

Abstract: Many biochemical pathways involved in hair and skin development have not been investigated. Here, we reported on the lesions and investigated the mechanism underlying hair and skin abnormalities in Zdhhc13(skc4) mice with a deficiency in DHHC13, a palmitoyl-acyl transferase encoded by Zdhhc13. Homozygous affected mice showed ragged and dilapidated cuticle of the hair shaft (CUH, a hair anchoring structure), poor hair anchoring ability, and premature hair loss at early telogen phase of the hair cycle, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Zdhhc13 mRNA expression in the epidermis has previously been confirmed using in situ hybridization (Liu et al, 2015). Here we studied lacZ expression in skin during embryogenesis using Zdhhc13 gene-trap mice (Zdhhc13 Gt/Gt mice), wherein the bacterial lacZ gene is under the regulation of the Zdhhc13 promoter (Saleem et al, 2010;Sutton et al, 2013).…”
Section: Epidermal Expression Of Zdhhc13 Can Prevent Skin Inflammationmentioning
confidence: 82%
See 2 more Smart Citations
“…Zdhhc13 mRNA expression in the epidermis has previously been confirmed using in situ hybridization (Liu et al, 2015). Here we studied lacZ expression in skin during embryogenesis using Zdhhc13 gene-trap mice (Zdhhc13 Gt/Gt mice), wherein the bacterial lacZ gene is under the regulation of the Zdhhc13 promoter (Saleem et al, 2010;Sutton et al, 2013).…”
Section: Epidermal Expression Of Zdhhc13 Can Prevent Skin Inflammationmentioning
confidence: 82%
“…In our previous genome-wide mouse ethylnitrosourea mutagenesis study, we identified homozygous mutant mice that had multiple skin phenotypes including cyclic alopecia, ragged hair coat, baldness, wrinkled skin, and acanthosis (Saleem et al, 2010). These phenotypes arose as a result of an A-to-T nonsense mutation in the Arg-452 codon of Zdhhc13; mice harboring this mutation are referred to as Zdhhc13 k/k (also known as Zdhhc13 skc4/skc4 ) mice (Liu et al, 2015;Saleem et al, 2010). In this study, we also generated Zdhhc13 knockout mice by crossing mice having exon 2 of their Zdhhc13 gene flanked by loxP sites (Zdhhc13 f/f mice, created using conventional gene-targeting) with E2A-Cre mice (Supplementary Figure S1a online) resulting in the deletion of Zdhhc13 exon 2 and the creation of a prematurely terminated protein of only 13 amino acids in length (Supplementary Figure S1b).…”
Section: Deficiency Of Zdhhc13 Causes Cyclic Alopecia and Ad-like Dermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of high cysteine contents in the absence of hard skin appendages may also point to a role of cysteine residues that is unrelated to disulfide bond formation. Cysteine residues have been identified as attachment sites for palmitic acid which allows the anchoring of proteins into membranes55. The process of cysteine palmitoylation has been demonstrated in mammalian skin proteins, but whether a similar process also occurs in snakes requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that ZDHHC13 is a novel regulator of postnatal skeletal development and bone mass acquisition via palmitoylation of MT1-MMP 29 . Moreover, ZDHHC13 is important for hair anchoring and skin barrier functions, likely mediated by the ZDHHC13 substrate, cornifelin 30 . Previously, we generated a Zdhhc13 -deficient mouse model through N-ethyl-N-nitrosourea (ENU) mutagenesis 31 .…”
Section: Introductionmentioning
confidence: 99%